2012
DOI: 10.1002/jwmg.409
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐contract management of Conservation Reserve Program grasslands provides benefits for ring‐necked pheasant nest and brood survival

Abstract: Conservation Reserve Program (CRP) fields may provide good habitat for nesting and brood‐rearing ring‐necked pheasants (Phasianus colchicus) during early stages of succession. But, the success of hens in early successional CRP, relative to late successional CRP and other grassland habitats, has yet to be evaluated. The reproductive period is especially critical for populations of pheasants, and CRP's benefits to hens and chicks may decrease as fields age because of loss of vegetative diversity, decrease in veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Sites used by brooding hens had greater forb content than randomly selected habitats with no other covariate having much effect (Tables 5 and 6). Most critically, hens appeared to be selecting habitat to maximize productivity: Matthews et al (2012) reported greater nest success and brood survival in managed CRP. County-level surveys of pheasants provide additional, demographic evidence for the benefits from such management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sites used by brooding hens had greater forb content than randomly selected habitats with no other covariate having much effect (Tables 5 and 6). Most critically, hens appeared to be selecting habitat to maximize productivity: Matthews et al (2012) reported greater nest success and brood survival in managed CRP. County-level surveys of pheasants provide additional, demographic evidence for the benefits from such management.…”
Section: Discussionmentioning
confidence: 99%
“…The 83-km 2 study area was located in the tallgrass prairie ecoregion in Stanton County (map: Matthews et al 2012). The landscape of our study area was dominated by agriculture (35.7%) and CRP fields (37.2%).…”
Section: Study Areamentioning
confidence: 99%
“…Conservation payments from the farm bill-which include most set-aside programs-are a major driver of idled land in agricultural landscapes (Burger et al, 2006). Long known to serve important functions for wildlife habitat, recent research on habitat management and biodiversity have increased the value of set-aside land for game and non-game species (Conover et al, 2011;Matthews et al, 2012). While our data show that set-aside land area has been subject to changes in the conservation or production focus of the farm bill, other work also suggests that the Conservation Reserve Program itself might have contributed to the decline of pastureland by increasing the net return of unenrolled, non-marginal cropland (Lubowski et al, 2008), thus increasing the incentive to convert pastureland to cropland.…”
Section: Idled Ground Pasture and Hay Groundmentioning
confidence: 99%
“…Several studies have been conducted to measure the success of wildlife management in the program (Dunn,, Stearns, Guntenspergen, & Sharpe, 1993;Giudice & Haroldson, 2007;Matthews, Taylor, & Powell, 2012;Negus, Davis, & Wessel, 2010;Swanson, Scott, &, Risley, 1999). Agency officials keep track of this data and sometimes help fund the research.…”
Section: Discussionmentioning
confidence: 99%
“…FSA has made considerable effort to try to reduce these negative effects by implementing adaptive conservation strategies and practices (USDA, 2012). However, further standards for maintaining and implementing conservation practices over the lifetime of the contracts could significantly improve environmental outcomes (Giudice & Haroldson 2007;Matthews et al, 2012;Negus et al, 2010;Osborne, Sparling, & Hopkins, 2012;Risley et al, 1999).…”
Section: Discussionmentioning
confidence: 99%